THE ROLE OF 'PEMAMOAN' IN THE WEDDING CUSTOMS OF THE KLÜET TRIBE IN THE VILLAGE OF RUAK, NORTH KLÜET SUB-DISTRICT, SOUTH ACEH REGENCY: PERAN PEMAMOAN DALAM ADAT PERKAWINAN SUKU KLÜET DI DESA RUAK KECAMATAN KLÜET UTARA KABUPATEN ACEH SELATAN - Masriati, Masriati; Muchsin, Misri A; Ahmad, Muhammad Yunus (Indonesian Journal of Islamic History and Culture, 2023)
This research aims to explain the role of pemamoan in the wedding customs of the Kluet tribe in the village of Ruak and the community's response to the role of pemamoan in the wedding customs of the Kluet tribe in the village of Ruak. The method used in this research is a qualitative, descriptive approach. Data collection techniques include observation, interviews, and documentation. The results of this research show that pemamoan is the uncle or male relative from the mother's side. Pemamoan plays a role in taking care of all the needs of the bride and groom, and the community of Ruak Village responds positively and accepts the role of pemamoan in the wedding customs of the Kluet tribe in the Village of Ruak, North Kluet Sub-district, South Aceh regency.